Plasmodium falciparum infections are associated with agglutinating antibodies to parasite-infected erythrocyte surface antigens among healthy Kenyan children. - Bull, P; Lowe, B; Kaleli, N; Njuga, F; Kortok, M; Ross, A; Ndungu, F; Snow, R; Marsh, K (2002)
Antibodies to the highly diverse variant surface antigens (VSAs) expressed on Plasmodium falciparum-infected erythrocytes are thought to play a role in the development of naturally acquired immunity to malaria. It has been suggested that children gradually acquire immunity through the piecemeal acquisition of antibodies to a large number of VSAs over several years of exposure. However, in a cross-sectional survey of Kenyan children before the malaria-transmission season, the proportion of children with antibodies recognizing randomly sampled VSAs was found to be strikingly higher among children with microscopically detectable P. falciparum infection, compared with those without detectable infection. We suggest that parasitization status may be an important consideration in longitudinal assessments of the protective role of some anti-parasite immune responses and support this suggestion with data from a prospective study of VSA antibodies in a group of children who subsequently had severe malaria.